Nogo receptor-Fc delivered by haematopoietic cells enhances neurorepair in a multiple sclerosis model. Issue 2 (4th April 2023) - Ye, Sining; Theotokis, Paschalis; Lee, Jae Young; Kim, Min Joung; Nheu, Danica; Ellen, Olivia; Bedford, Thomas; Ramanujam, Padmanabhan; Wright, David K; McDonald, Stuart J; Alrehaili, Amani; Bakhuraysah, Maha; et al.
Abstract: Nogo receptor 1 is the high affinity receptor for the potent myelin-associated inhibitory factors that make up part of the inflammatory extracellular milieu during experimental autoimmune encephalomyelitis. Signalling through the Nogo receptor 1 complex has been shown to be associated with axonal degeneration in an animal model of multiple sclerosis, and neuronal deletion of this receptor homologue, in a disease specific manner, is associated with preserving axons even in the context of neuroinflammation. The local delivery of Nogo receptor(1-310)-Fc, a therapeutic fusion protein, has been successfully applied as a treatment in animal models of spinal cord injury and glaucoma. As multiple sclerosis and experimental autoimmune encephalomyelitis exhibit large numbers of inflammatory cell infiltrates within the CNS lesions, we utilized transplantable haematopoietic stem cells as a cellular delivery method of the Nogo receptor(1-310)-Fc fusion protein. We identified CNS-infiltrating macrophages as the predominant immune-positive cell type that overexpressed myc-tagged Nogo receptor(1-310)-Fc fusion protein at the peak stage of experimental autoimmune encephalomyelitis. These differentiated phagocytes were predominant during the extensive demyelination and axonal damage, which are associated with the engulfment of the protein complex of Nogo receptor(1-310)-Fc binding to myelin ligands. Importantly, mice transplanted with haematopoietic stem cells transduced with the lentiviral vector carrying Nogo receptor(1-310)-Fc and recovered from the peak of neurological decline during experimental autoimmune encephalomyelitis, exhibiting axonal regeneration and eventual remyelination in the white matter tracts. There were no immunomodulatory effects of the transplanted, genetically modified haematopoietic stem cells on immune cell lineages of recipient female mice induced with experimental autoimmune encephalomyelitis. We propose that cellular delivery of Nogo receptor(1-310)-Fc fusion protein through genetically modified haematopoietic stem cells can modulate multifocal experimental autoimmune encephalomyelitis lesions and potentiate neurological recovery. Abstract : Nogo receptor 1 can bind myelin-associated inhibitory factors that constitute part of the extracellular milieu during experimental autoimmune encephalomyelitis to signal axonal degeneration. Ye et al . report that genetically modified transplantable bone marrow stem cells can deliver the Nogo receptor-Fc therapeutic protein and promote neurorepair during experimental autoimmune encephalomyelitis. Graphical Abstract: Graphical Abstract